The role of the teacher in the physical education of preschool children - Zayas Acosta, Rasciel de la Caridad (Avances en Supervisión Educativa, 2017)
Today the educational attention to the children of the pre-school childhood assumes a position on the physical education. In the present article the analysis of published studies on the subject is carried out. The information collected and the empirical evidence attest to the transformations that must be made in the work of teachers to adapt to this reality and be prepared to achieve the integral development of children in preschool children. Therefore, the objective of the article is to propose how to strengthen the role of teachers to contribute to enhance physical education in preschool children.